Tests, measurements, and selection in the Belgian Congo during the 1950s: the end of racist clichés?. (4th May 2019) - Depaepe, Marc
ABSTRACT: Research into the history of colonial education in Congo has shown that, for a long time, it was dominated by the idea of gradual development of the masses. Here, the problem of selecting an intellectual elite hardly arose. It was only in the 1950s that a growing number of voices began to clamour for the Congolese to be permitted to study in secondary schools and universities. However, psychological testing was not the first means of resort in the selection of an elite. Nevertheless, following the Second World War, the sentiment that psychological testing might be helpful began to take hold in Belgium. Drawing on various international developments, a handful of specialists took up the issue. The analysis of their work shows that much of what Linstrum contended concerning the history of psychological research in the British Empire, also applies to Congo. Despite their modest number, these studies cannot simply be viewed as pretext for the racism deeply ingrained in colonial circles. But this does not mean that pseudo-scientific clichés about the backwardness of the Africans did not make an appearance. Rather the contrary was true. In any event, these studies were not prepared to pierce through general sentiment and therefore, do not seem to have yielded much more than adherence to the new, prestigious scientific research methods.